PENGARUH BEBAN KERJA DAN BURNOUT TERHADAP KINERJA KARYAWAN PT PUTRATAMA BHAKTI SATRIA CISAUK BSD TANGERANG - Aji Pullah; Rahmi Andini Syamsuddi (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
The objective of this study is to determine whether training and human resource (HR) competencies have a partial or simultaneous effect on employee performance at PT Dharma Karyatama Mulia, East Jakarta. This research employs a quantitative method with an associative approach. The sampling technique used is saturated sampling, with a total population as well as a sample of 57 employees. Data were collected through questionnaires and analyzed using instrument testing, descriptive statistics, classical assumption tests, statistical tests, and hypothesis testing with the assistance of SPSS version 26. The results of the study indicate that training and HR competencies have a positive and significant effect on employee performance. The t-value for the training variable is 2.616, which is greater than the t-table value of 2.004, with a significance value of 0.000 < 0.05. This demonstrates that training has a positive and significant effect on employee performance. Furthermore, the t-value for the HR competency variable is 4.363, which is also greater than the t-table value of 2.004, with a significance value of 0.000 < 0.05, indicating a positive and significant effect of HR competencies on employee performance. Simultaneously, training and HR competencies have a positive and significant effect on employee performance, as reflected in the regression equation Y = 6.331 + 0.318(X₁) + 0.531(X₂). The correlation coefficient (R) is 0.896, indicating a very strong relationship between training and HR competencies and employee performance. The coefficient of determination and the F-test results show that the calculated F-value is greater than the F-table value (108.521 > 3.170), supported by a significance value of less than 0.05 (0.000 < 0.05). These findings confirm that training and HR competencies jointly have a significant influence on employee performance. Keywords: Training, Human Resource Competency, Employee Performance